Clinical Features of Pediatric Complex Regional Pain Syndrome: A 5-Year Retrospective Chart Review. Issue 12 (December 2019) - Mesaroli, Giulia; Ruskin, Danielle; Campbell, Fiona; Kronenberg, Sefi; Klein, Sara; Hundert, Amos; Stinson, Jennifer
Abstract : Objectives: Complex regional pain syndrome (CRPS) is a painful condition of a limb characterized by a constellation of symptoms. Little is known about the clinical features of pediatric CRPS, with fewer than a dozen studies published to date. The aim of this study was to explore the clinical course of pediatric CRPS, with emphasis on clinical features and disease outcomes. A secondary aim was to discern differences in clinical features of pediatric CRPS with and without related movement disorders, and between children who had a favorable and unfavorable outcome. Materials and Methods: We carried out a retrospective chart review of children with CRPS who presented to a pediatric Chronic Pain Clinic in Canada over a 5-year period (2012 to 2016). Results: The study identified 59 children with CRPS (mean age: 12.7±2.5; 74.6% female; 72.9% lower extremity). In total, 87% (n=48) of children experienced complete resolution or significant improvement of CRPS, with a relapse rate of 15%. Overall, 25% (n=15) had a CRPS-related movement disorder. There were no differences in the clinical features of pediatric CRPS with or without related movement disorders. Children who experienced a favorable outcome had a significantly shorter symptom duration at the initial visit in comparison with children who experienced an unfavorable outcome. Discussion: In this cohort, pediatric CRPS was most common in girls around the age of 12, usually in the lower extremity, and most experienced a favorable outcome. Further research is needed to better understand the prognosis and relapse rate of pediatric CRPS.